SOCIAL MEDIA CONTENT MANAGEMENT ON INSTAGRAM @VISITINGJOGJA AS OFFICIAL MEDIA CHANEL OF YOGYAKARTA TOURISM BOARD DURING COVID-19 PANDEMIC - Siti Chotijah; Diyah Indiyati; Muhlis; Hartin Nur Khusnia (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Tourism is the most affected sector by the Covid-19 pandemic. New normal paradigms require adaptations and innovation especially for communication. The Covid-19 pandemic has been changes marketing paradigms, media strategies and tourism promotion methods. Yogyakarta is the second popular destination in Indonesia after Bali. @Visitingjogja as the official Instagram account of the Yogyakarta provincial tourism office has changed the management of social media content as an effort to deal with the Covid-19 pandemic. This change was made to accommodate information needs, adjust conditions and fulfill public information in terms of tourism during the Covid-19 pandemic. This research was conducted in 2021 for 6 months from March to August with a qualitative descriptive research approach. Data collections used in this research were the observation method on the @visitingjogja account and in-depth interviews with the head of tourism information staff and social media admins. The results of this study show about changing of human resource team during pandemic with skill and specialization for social media strategic, changing the management technique, and changing the social media content. @visitingjogja changed its contents from destination and event promotion to public policy for tourism sector during Covid-19 pandemic like vaccination programs, health protocols with various contents like videos, photos and Instagram reels. Social media algorithm, impression and public respond are the most affected in content management by the weekly evaluation.